A new analytical approach to determine slotting based eddy current losses in permanent magnets of PMSM taking into account axial and circumferential segmentation. Issue 2 (2nd March 2015) - Bode, Cornelius; Canders, Wolf-Rüdiger; Henke, Markus
Abstract : Purpose: – The purpose of this paper is to calculate slotting-based eddy currents in permanent magnet excited synchronous machine (PMSM) taking into account axial and circumferential segmentation of magnets. Design/methodology/approach: – An analytical approach to calculate eddy current losses in PM caused by slotting harmonics of PMSM is presented. The eddy current reaction field is taken into account as well as axial and circumferential segmentation of the magnets. Findings: – The analytical model provides results comparable to 3D-FEM calculations even at high frequencies at reduced computation costs. To generalize the results the magnetic Reynold's number is introduced. Originality/value: – Taking into account the axial and circumferential segmentation in the PDE; the approach is much more accurate compared to known approaches; accuracy is comparable to 3D-FEA.